2019
DOI: 10.1177/1046878119866878
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Mental Health Objective Structured Clinical Examination (OSCE): A Pilot Study

Abstract: Background.An Objective Structured Clinical Examination (OSCE) is an effective means for clinical evaluation related to clinical competence. Historically, clinical assessment is based on direct observation which can be rooted in subjectivity. Evidence is minimal regarding psychometric properties of an OSCE in undergraduate mental health nursing education, although established as a valid measure of clinical competence. Method.A pilot study was conducted with a convenience sample of 13 sixth semester nursing st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
16

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 31 publications
0
6
0
16
Order By: Relevance
“…[ 29 ] Only Stockman et al . [ 13 ] presented criterion validity, but the questionnaire used (Pierr et al . questionnaire 2004) as criterion had no validity and reliability.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…[ 29 ] Only Stockman et al . [ 13 ] presented criterion validity, but the questionnaire used (Pierr et al . questionnaire 2004) as criterion had no validity and reliability.…”
Section: Resultsmentioning
confidence: 99%
“…Data were extracted according to the following topics: The purpose of the study, the target population, the main findings, and the instrument characteristics [ Table 1 ]. [ 13 26 27 28 29 30 ]…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As noted by the researchers (Stockmann et al, 2019) in our next article, the assessment process that accompanies direct observation can be subjective. The researchers observed that Objective Structured Clinical Examinations (OSCE) have been used Table 1.…”
mentioning
confidence: 99%